Text readability and fraud detection / Intan Waheedah Othman, Hazlina Hassan and Dr. Roszana Tapsir - Othman, Intan Waheedah; Hassan, Hazlina; Tapsir, Roszana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Our study examines the readability of qualitative text in company annual reports in the attempt to detect fraud. The management obfuscation theory predicts that the management of a badly performed company tends to hide bad news by decreasing the readability of financial reports. Thus, it is believed that there could have been hidden clues in the narrative disclosures that can be indicators of fraud. This study examines the application of a readability index tool as a proactive means in identifying fraud. The methodology is developed by using the Coh Metrix version 2 indices - Flesch Reading Ease Score Formula. Our findings show that prior to the fraud conviction, fraud firms have been using complex text readability. As such, this fraud detection technique may be of significance in assisting the auditors and other stakeholders in their assessment of a company. Findings of this study may give light to exploring further linguistic feature that can distinguish the fraudulent annual reports from those non-fraudulent annual reports.